54.6k views
1 vote
HELP PLEASE ASAP 20 points

HELP PLEASE ASAP 20 points-example-1
User Jorgeca
by
5.8k points

2 Answers

1 vote

Answer:

D. x^2 - 6x + 7 = 0.

Explanation:

The roots are 3 plus or minus sqrt(2). That means the equation is...

(x - [3 + sqrt(2)]) * (x - [3 - sqrt(2)])

= [x - 3 - sqrt(2)] * [x - 3 + sqrt(2)]

= x^2 - 3x - xsqrt(2) - 3x + 9 + 3sqrt(2) + xsqrt(2) - 3sqrt(2) - (sqrt(2))^2

= x^2 - 3x - 3x + 9 - 2 - xsqrt(2) + xsqrt(2) + 3sqrt(2) - 3sqrt(2)

= x^2 - 6x + 7.

Hope this helps!

User Cory Madden
by
5.6k points
5 votes

Answer:

Its d
x^(2) -6x+7=0

Explanation:

A=
2+√(3\\)

B=
3√(2)

C=
-3+√(2)

User Patience
by
5.1k points